(untitled) (Modern education and development, 2025)
By offering cutting-edge learning resources, improving academic achievement, and equipping students for a technologically advanced future, artificial intelligence (AI) is revolutionizing students’ lives. AI-powered apps promote creativity and critical thinking by enabling rapid feedback, individualized learning experiences, and efficient time management. Additionally, AI facilitates accessibility, enabling high-quality education for kids with a range of needs. This study examines the various ways artificial intelligence (AI) is affecting education and how it might completely transform the way that people learn.